Classifying the Incidence Rates of Cancers Using Data Mining Techniques (Perspective to Gas Leakage Accident of Bhopal City) - Gour, Sanjeev (International Journal of Computer Sciences and Engineering, 2025)
Cancer is one of most dangerous diseases and the incidence rate of cancer in India is increasing every year. Today, number of tools and techniques are available to analyze large cancer dataset. Data mining tools are most frequently used to identify patterns in cancer patients and in cancer diagnosis or detection. Data mining is now widely used in health care industry as it has a great capability to extract hidden patterns from the large past medical record of cancer patients. This study uses Data Mining techniques called Classification and Clustering to classify and compare the incidence rates of TCR (Tobacco Related Cancer) and Non-TCR (Non-Tobacco Related Cancer) in two areas of Bhopal city and extracted some useful and interesting fact from the incidence rates data of cancer patients. The incidence rate data of cancer were obtained during past 40 years from Bhopal-population-based cancer registries (PBCR) of two areas partitioned after Gas tragedy of Bhopal city. This study can be helpful to the medical analysts as a decision support system. The study was done using WEKA Tool.